3D City Online Visualization and Cluster Architecture for Digital City. (5th November 2021) - Fu, Lin; Ding, Yaqing
Abstract : As an important carrier of human production, life, and social development, the emergence of cities symbolizes the maturity and civilization of mankind. For more than 40 years of reform and opening up, our country's economic development has become increasingly prosperous, and urbanization is booming. At present, our country is in a decisive period for building a well-off society in an all-round way, with rapid progress in socio-economic growth and urbanization. Based on this, this article is oriented towards urban visualization modeling work and proposes a cluster modeling method that is compatible with the combination of urban geological structure and three-dimensional urban space, so that urban space modeling work not only pays attention to the rationality of above-ground planning and construction but also fully considers underground geology the stability and safety of the structure. This paper uses the 3D city online visualization modeling technology to efficiently and reasonably complete the 3D urban geological modeling under the fusion of multiple geological data and combines the organic combination of multisource heterogeneous model data to convert the geological model data into a 3D geographic information model; the universal standard format analyzes the rapid construction of large-scale complex geological structure models and the integrated expression of multisource heterogeneous model data. Experiments have proved that from the cluster capacity of 5, 000 to 100, 000, no matter how much the modeling time is different, whether it is to search the entire territory or part of the scope, the search time of the 3D city visualization model is less than 20 ms, and the 3D city visualization model map of the city can be well established. This shows that the three-dimensional city visualization model highlights the impact of the urban geological environment on urban construction and development and visually and vividly displays region geological structure and other information in a three-dimensional way, providing corresponding information for urban geological stability assessment and geological disaster rescue reference and help.